Examining Customer Loyalty in the Children's Clothes Segment of Matahari Department Store in Indonesia - Suwarno, Bambang; Alya, Soraya (International Journal of Social Science and Business, 2024)
The children's fashion retail industry is very competitive. As a retailer, Matahari Departement Store needs to consider which customer experience elements drive customer satisfaction and loyalty to the children's clothes brand Donita in Medan. This research aims to determine whether the quality of children's clothes retail products will influence customer satisfaction and loyalty when buying at retailers. This research design is quantitative with associative causality research and a non-probability purposive sampling method. One hundred questionnaires can perform descriptive statistics by processing data for the SMARTPLS method. The research results show that all variables have a positive and significant effect. Customers expect quality children's clothes products to perform well, and aesthetics and models have good resistance to satisfaction (t-statistic value 17.738) and customer loyalty (t-statistic value 8.643). Customers will be more loyal if their expectations are met from the perception of the quality and value of the clothes they buy (t-statistic value 5.065). So, it can be concluded that loyalty will be higher if satisfaction with product quality has been appropriately met. The novelty of this research is that even though children's clothes customers are loyal to a brand/product, repeated purchasing decisions do not occur when the product design/model is not liked. The quality of the clothing is poor because the dress's color fades quickly.